2023
DOI: 10.3390/ijms24021031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating lncRNA Expression Patterns during HIV-1 Treatment Interruption

Abstract: Lately, the interest in long non-coding RNAs (lncRNAs) as potential drug targets and predictive markers in the context of HIV-1 has peaked, but their in vivo expression and regulation remains largely unexplored. Therefore, the present study examined lncRNA expression patterns during a clinical antiretroviral treatment interruption (ATI) trial. Peripheral blood mononuclear cells were isolated from ten patients at four timepoints: prior to ATI, 7–15 days after stop, at viral rebound and 3 months post antiretrovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Several lncRNAs in this study displayed pronounced aberrant expression patterns during HIV-1 infection, and these lncRNAs returned to normal expression levels following ART. Consistent with our findings in the present investigation, Zhaou et al found a restoration in the level of lncRNAs with therapy [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several lncRNAs in this study displayed pronounced aberrant expression patterns during HIV-1 infection, and these lncRNAs returned to normal expression levels following ART. Consistent with our findings in the present investigation, Zhaou et al found a restoration in the level of lncRNAs with therapy [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, circulating lncRNAs that are detectable by qPCR and originate from cell-derived microvesicles, exosomes, apoptotic vesicle bodies, and other undiscovered routes may be used as possible indicators of HIV-1 infection. Circulating lncRNAs have been discovered in a few studies that may act as biomarkers for HIV-1 infection [ 23 , 49 , 50 ]. None of the earlier reports have evaluated the ability of circulating lncRNAs to detect both the eclipse stage and the acute/early stage of HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%